Between environmental coloniality and forest knowledge: Amazonian challenges towards COP-30 (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It offers a decolonial analysis, situating the debate between environmental coloniality and the knowledge of the forest. It claims recognition of the Amazon as a political and epistemic subject, warning of the risks of a merely discursive visibility of the region.(Received: September 2025 | Accepted: October 2025)
Keywords: Decoloniality; Amazon; Traditional Knowledge; Environmental Coloniality; Epistemology